Prognostic significance of tumor burden assessed by whole-body magnetic resonance imaging in multiple myeloma patients treated with allogeneic stem cell transplantation - Mosebach, Jennifer; Shah, Sofia; Delorme, Stefan; Hielscher, Thomas; Goldschmidt, Hartmut; Schlemmer, Heinz-Peter; Schönland, Stefan; Hegenbart, Ute; Hillengaß, Jens (Haematologica, 2018)
Allogeneic stem cell transplantation is a therapeutic option under dispute but nonetheless chosen with increasing frequency for patients suffering from multiple myeloma in Europe. To study possible predictors of survival, 79 patients were investigated using whole-body magnetic resonance imaging to assess the visible tumor burden before and after allogeneic stem cell transplantation. Statistical analysis of clinical and imaging parameters included Cox regression models and distribution of survival time estimates (Kaplan-Meier method). Log rank test was used to determine the prognostic impact of the presence of focal lesions on survival. A higher tumor burden according to the lesion count was associated with a shorter overall survival (univariable/multivariable Cox regression: 1st magnetic resonance imaging P=0.028/P=0.048; 2nd magnetic resonance imaging P=0.008/P=0.024). Focal infiltration pattern itself seemed to be an additional adverse prognostic factor for overall survival (2nd MRI P=0.048), although no definite cut-off could be defined. Kaplan-Meier estimates at 60 months of follow up show a significant difference (Log rank P=0.04) for overall survival rates between patients with focal infiltration (32%) and those without (75%). Since this subgroup of patients may benefit from maintenance therapy, adoptive immunotherapy, or local interventions, whole-body imaging is an appropriate and highly recommendable diagnostic approach for detection of prognostically relevant lesions before and after treatment.